Teaching NeuroImage: Bilateral Nucleus Tractus Solitarius Lesions in Neurogenic Respiratory Failure. (4th January 2022) - Parayil Sankaran, Bindu; Wortman, Saskia B.; Willemsen, Michel A.; Balasubramaniam, Shanti
Abstract : A 7-year-old girl with MEGD(H)EL [3-methylglutaconic aciduria, dystonia-deafness, (hepatopathy), encephalopathy, Leigh-like syndrome, SERAC1] 1 presented with worsening respiratory compromise. The evaluation showed type II respiratory failure (e.g., hypercapnic) necessitating mechanical ventilation. Cerebral MRI demonstrated progression of known changes in MEGD(H)EL (Figure, A and B) and symmetric nucleus tractus solitarius (NTS) involvement (Figure, C and D). She was ventilator dependent and subsequently died from the effect of the disease.